Microbiology of periprosthetic infections following implant-based breast reconstruction surgery: a multicentric retrospective study - Lisa, Andrea Vittorio Emanuele; Zeneli, Flavia; Mazzucco, Martina; Barbieri, Benedetta; Rietjens, Mario; Lissidini, Germana; Vinci, Valeriano; Bartoletti, Michele; Belati, Alessandra; Bavaro, Davide (Frontiers in Surgery, 2024)
IntroductionImplant-based breast reconstruction (IBR) is the predominant breast reconstruction technique post-mastectomy, with bacterial infections being a significant complication affecting patient recovery and quality of life. The following study aimed to determine the microbiological features of the causative agents responsible for breast implant infections, with more attention paid to the comparative analysis of Gram-positive and Gram-negative bacteria and their presentation.MethodsWe conducted a retrospective analysis of 214 patients who presented with periprosthetic infection and underwent implant removal following implant-based breast reconstruction at Humanitas Research Hospital and Istituto Europeo di Oncologia between January 2018 and March 2024.ResultsThe study revealed that Gram-positive bacteria were more prevalent, with Staphylococcus species, particularly Staphylococcus aureus, being the most isolated pathogen in both institutions (∼39.96%). In contrast, Gram-negative bacteria were less frequent, with a higher proportion of these pathogens being multi-resistant strains. A significant difference was observed (p = 0.007), indicating that individuals with normal BMI have a higher prevalence of Gram-positive infections (88.46%), whereas obese and overweight patients had higher proportions of Gram-negative infections (23.53% and 28.89%, respectively). In addition, smoking status was also significantly associated with pathogen distribution (p = 0.032), with active and past smokers being related to higher percentages of polymicrobial infections. Furthermore, positive prophylactic MSSA/MRSA swabs were significantly more associated with Staphylococcus aureus infections compared to those with negative results (p = <0.001).ConclusionsGram-positive bacteria, especially Staphylococcus species, dominate the microbiological landscape of implant-based breast reconstruction (IBR) infections. Our findings provide insights into this critical issue, facilitating a more precise choice of empiric antibiotic treatment and prevention strategies. This analysis underscores the necessity for prophylactic protocols and therapeutic approaches tailored to the predominant bacterial groups. Further research is needed to explore long-term trends and resistance mechanisms to improve patient management.